A Package of Policies to Permanently Increase Output Without Inflation - Kenneth Koford (Levy Economics Institute of Bard College, 1991)
Economists have searched for policies that concurrently establish full employment with stable prices and high output. The supply side theorists of the 1980s claimed they could produce increased output with lower inflation: The crux of their argument is that "taxes and subsidies create a wedge between the private and social returns from productive activities. As people follow the maximum private return, they reduce society's welfare due to this wedge. Thus, policies that reduce these tax-subsidy wedges will reduce inefficiency and increase output." In the aftermath of failed supply side predictions, new classicals have dismissed high unemployment and aggregate instability as actual problems. Meanwhile, new Keynesians have yet to develop a model that demonstrates the macroeconomic problem or a means to reduce unemployment. It is submitted that both a market anti-inflation plan (MAP) and tax-based incomes policy (TIP) simultaneously reduce inflation and increase output- however, the link to output may be indirect. MAP and TIP increase supply by reducing externalities in the economy, specifically by reducing firms' market power. Hence, there is an underlying symmetry between incentive anti-inflation plans and incentive supply-increasing policies. In sum, an integrated package of policies is proposed that yields full employment with stable prices by using fundamental procedures of internalizing externalities.
Keywords: 330